Meaning and its impact on aesthetic reception - Hussein Al-Khafaji, Zeena Ghani (Opción, 2019)
There is no doubt that the literary text, whether it is poetry or rhetoric, invol- ves a meaning considering it a speech on one hand and an aesthetic artistic touch that adds to its beauty through centering it, i.e. consistent and coherent construction of the meaning in a manner that ensures its life and novelty and attraction of the reader on the other hand. Literary text has many features that make it the main text of many texts that are parallel in it or equivalent to it after the meaning supersedes the words referring to it to transform into a second, a third and possible meaning through visible relations that sometimes grant the plain text a shape and sometimes contribute through non-visible relations in generating connota- tions and creating new textual spaces. It is natural that the aim of this research is to achieve the critical thought with reference to the characteristics of each literary school in terms of (reception) concept and show reasons of comparing this concept between the theory pioneers and significant figures of our criticism science like: Al-Jahiz, Abdulqaher Al-Jurjani and Al-Qartajni. Perhaps some of the factors that forced us to demonstrate the opinions of those critics are what we found within the contents of the new theory regarding the thought that has no reference except in our criticism credit and therefore, it is necessary to divide the research into four axes: meaning concept, reception aesthetics, meaning in literary texts and interpretive meaning.